Effect of Methotrexate Injection on Orthodontic Tooth Movement: An Experimental Study on Rats - Amin Golshah (Hindawi Limited, 2021)
Introduction. Knowledge about the effects of medications, vitamins, and various supplements on orthodontic tooth movement (OTM) is imperative for orthodontists. This study aimed to assess the effect of methotrexate (MTX) injection on OTM in rats. Materials and Methods. Twenty-eight male Wistar rats were randomized into four groups (n = 7). The first molar and central incisor were connected using a nickel-titanium (NiTi) coil spring with a 50 g load in each rat. The two experimental groups received 0.75 mg/kg and 1.5 mg/kg MTX, respectively, intraperitoneally for 21 days. The negative control group did not receive any injection and did not undergo orthodontic treatment. The positive control group underwent orthodontic treatment and received 0.9% saline (NaCl) injections for 21 days. All rats were sacrificed with chloroform inhalation after 21 days; their maxilla was resected, and the mean number of Howship’s lacunae, blood vessels, osteoclasts, and resorption lacunae was counted. The reduction in bone volume (bone volume to total volume ratio (BV/TV)) at the site of the maxillary molar was quantified by microcomputed tomography (micro-CT). Results. OTM, the number of osteoclasts, and the number of blood vessels significantly increased in rats treated with MTX (P<0.05). However, the increase in the number of Howship’s lacunae and resorption lacunae was not significant (P>0.05). Lower BV/TV in the MTX groups was in agreement with the increased number of osteoclasts. Conclusion. Injection of MTX can significantly increase OTM and decrease root resorption in rats.